Kaupapa Māori practitioner's whakaaro (thoughts) of traditional practices (rongoā, rāranga, mirimiri and pūrākau) assisting rangatahi Māori (Māori youth) with suicidal behaviours : a thesis presented in partial fulfillment of the requirements for the degree of Master's of Science in Psychology at Massey University, Wellington, New Zealand - Gemmell, Joanna (Massey University, 2020)
Worldwide, a person dies by suicide every 40 seconds (World Health Organization, 2018). An estimated 793,000 people take their lives by suicide every year, and for every one suicide, 20 more people attempt suicide (World Health Organization, 2018). Internationally, for the younger generation aged 15–29 years, suicide is the second most prominent cause of death (World Health Organization, 2018). In Aotearoa (New Zealand), the Māori (Indigenous people) population has an approximate average age of 22 (Statistics New Zealand, 2017) and we are losing rangatahi Māori (Māori youth) to suicide at almost double the rate than their non-Indigenous counterparts (aged 15–24) (Ministry of Health, 2015; World Health Organization, 2018). Western attempts at suicide prevention lack cultural specificity, while Indigenous suicide prevention methods focus on reconnection back to culture, cultural living and traditional practices. Māori practitioners whakaaro (thoughts) show traditional Māori practices of rāranga, pūrākau, mirimiri and rongoā have beneficial properties that alleviate suicidal behaviours. This project incorporates an overarching Kaupapa Māori methodology while integrating qualitative research and semistructured interviews offers flexibility, subjectivity and to extract rich whakaaro for an experiential thematic analysis approach. Seven wāhine (female) Māori practitioners were interviewed. Findings show three critical whakaaro that can assist rangatahi Māori wellbeing: i) Healing as a Whole, ii) Protecting with Wairua and iii) Self-Healing. This study offers mental health professional’s valuable insight into utilizing Māori practitioners as a viable culturally appropriate method for positively promoting Māori wellbeing and protective factors that may prevent suicide. Future research could explore traditional practices as alternative treatment for whānau (family) who have experienced or supported tāngata (people) with suicidal behaviours.
Keywords: Māori Masters Thesis; 451014 Ngā pūnaha mātauranga hinengaro o te Māori (Māori psychology knowledge systems)